Legal Analysis of Legal Personality Organization of South East Asian Countries (ASEAN) as the Subject of International Law - Satesna, Dhezya Pandu (Universitas Negeri Semarang, 2019)
ASEAN stands on August 8, 1967, under the agreement of five foreign ministers of Southeast Asian Countries namely Adam Malik (Indonesia), Tun Abdul Razak (Malaysia), Thanat Khoman (Thailand), Rajaratnam (Singapore), and Narcisco Ramos (Philippines). The ASEAN Charter is the legal and institutional framework that binds all ASEAN member countries and makes ASEAN an organization of legal status. ASEAN has immunities and privileges in the territory of the Member States as necessary to achieve its objectives. ASEAN with the ASEAN Charter being a full international organization, there are clear rules on ASEAN. Among them are the privileges and immunities for Permanent Representatives and diplomatic diplomatic agents in the ASEAN Secretariat.